Development of Managerial Skills for Success in a Dynamic Business Environment - Dhuniganh, Ranesh; Anjali, Niya; Samarthy, Josh (Journal Development Manecos, 2024)
This paper describes the process of managerial skill acquisition regarding the challenges and opportunities that arise from a changing environment. It highlights executive skills that include technological expertise, cultural sensitivity, leadership adaptability, analytical ability, and responsible management. Reporting the study as a quantitative research, data was sung from 250 managers in different industries using a structured questionnaire and analysed using SPSS version 26. The findings highlighted suggest there is significant positive relationship between managerial competencies and organizational performance. Technological skills and utilization of information in decision-making process demonstrated the highest levels of correlation with innovation and strategic performance. Furthermore, cultural awareness and managerial adaptability were critical when doing business in the increasingly integrated global economy and diverse employees. It was established that sustainability and ethical leadership positively influence corporate social responsibility and the longevity of business operations. In doing so, these findings enrich current literature by filling voids regarding the exact consequences of these competencies in modern management environments. Thus, the study draws the conclusion that managerial competencies should be an ongoing process which assists organizations to remain competitive and relevant in an evolving global economy. Subsequent research may examine the relationship and the specific implications of current up-and-coming technologies on different, more particular fields for managerial competencies.